Pembangunan Mobile GIS Analisis Tutupan Lahan pada Kabupaten Trenggalek - Ramadhan Abdurrahman Mukhtar; Fatwa Ramdani; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Land use and land cover is important in understanding the human activities with the environment. Trenggalek regency agricultural potential is a potential that support the economy. Development in the trade industry sector is also increasing the lead to endangerment of the availability of agricultural land if it is not managed properly. Endangerment of food resistance, loss of livelihood of farmers and the loss of agricultural infrastructure is an example of the impact of conversion of agricultural land into non-agricultural. The need for geographic information and updates are very important in land management and field operations. In this study constructed a mobile GIS application for the analysis land cover and land use in Trenggalek regency. This application is built using hybrid technology with HTML5, CSS and javascript. In this research will help to provide information about land use and land area of ​​the period 2014, 2015 and 2016 and also information of farmland protected area regulations or Lahan Pertanian Pangan Berkelanjutan (LP2B). This study uses a semi-automatic classification plugin (SCP) is a Quantum GIS plug-in to process and classify satellite image data. Satellite imagery used include sentinel-2 2016, Landsat-8 in 2015 and 2014. Spatial data that are already classified will be exported and displayed on mobile devices android and ready to used as a reference in the field operations. With the information directly from mobile device expected governmental Trengggalek easier to manage land for future development and Trenggalek people also more selective in choosing and using the land.